1985
DOI: 10.1007/bf01469632
|View full text |Cite
|
Sign up to set email alerts
|

An adsorption effect on the gel strength of dilute gelatin-stabilized oil-in-water emulsions

Abstract: Abstract:The incorporation of emulsion oil droplets into a gelatin gel leads to an initial increase in shear modulus at 25 ~ for a gelatin concentration of 8 wt % but an initial decrease for a concentration of 5 wt %. The latter resuIt is consistent with a net lowering of the gelatin concentration available for gelation in the aqueous phase due to adsorption at the oil-water interface.Key words: Gelatin, emulsion, gel, shear modulus, adsorption.Incorporating filler particles into a gelatin gel matrix normally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…In all gels, there was an increase in G 0 with oil content and time. Differences in G 0 with 4 wt% oil were minimal, similar to observations by Dickinson, Stainsby, and Wilson (1985) who worked on 5 wt% gelatin oil-filled gels. Though addition of oil containing polysorbate 20 also led to large increases in rigidity, its presence reduced G 0 in comparison to the gels with no surfactant (Fig.…”
Section: Confocal Microscopysupporting
confidence: 84%
“…In all gels, there was an increase in G 0 with oil content and time. Differences in G 0 with 4 wt% oil were minimal, similar to observations by Dickinson, Stainsby, and Wilson (1985) who worked on 5 wt% gelatin oil-filled gels. Though addition of oil containing polysorbate 20 also led to large increases in rigidity, its presence reduced G 0 in comparison to the gels with no surfactant (Fig.…”
Section: Confocal Microscopysupporting
confidence: 84%
“…For active filler particles, as in the case of gelatinbased emulsion gels, a droplet modulus higher than the modulus of the continuous phase leads to an increase in composite modulus as a function of oil content, and vice versa. This was confirmed in a study by Dickinson et al (1985), in which increasing shear modulus with increasing oil content for a gelatin emulsion was observed.…”
Section: The Effect Of Oil Content and Droplet Sizesupporting
confidence: 80%
“…At low concentrations of gelatin, this effect can be significant, with decreasing shear modulus and even a potential loss of gelling ability at higher oil concentrations (Dickinson et al, 1985).…”
Section: The Effect Of Oil Content and Droplet Sizementioning
confidence: 99%
“…At gelatine concentration higher than 2.5 wt%, aggregation of emulsion droplets was visible which could be related to the higher storage modulus of the gelled emulsion compared to simple gelatine gels. Previous studies have shown that incorporation of particles or oil droplets could lead to an increase in gelatine gel rigidity depending upon the gelatine concentration (53,63). Oil droplets seem to contribute to the stiffening of the gel as they are mechanically connected to the gel matrix and so contribute to the gel strength (52).…”
Section: Viscoelastic Properties Of Gelled Emulsionmentioning
confidence: 99%